Dinamika Aktor dalam Politik Kebijakan Penutupan Rumah Ibadah Studi Kasus Gereja Kristen Indonesia (GKI) Yasmin, Kota Bogor Tahun 2006-2022 - Bening, Reyni Neviari (Socio-political Communication and Policy Review, 2025)
The dynamics of actors in the policy of closing the Indonesian Christian Church (GKI) Yasmin’s place of worship in Bogor City during the period of 2006-2022. The focus of this research is to analyze the roles of key actors, the factors causing conflicts, and the policy’s impact on religious freedom in Indonesia. This research employs a qualitative approach with a case study method involving in-depth interviews, observations, and document analysis. The findings reveal that the conflict arose due to alleged administrative violations in the submission of the Building Permit (IMB), community resistance to the church’s presence, and local government policies that failed to support diversity. Other influencing factors include a lack of public education about the importance of religious tolerance and weak communication between the government, the community, and GKI Yasmin congregation. The conflict reflects majority-minority tensions exacerbated by inadequate regulations regarding the establishment of places of worship. The Supreme Court’s ruling in favor of GKI Yasmin could not be implemented due to social and political pressures at the local level. Resolving the conflict through legal means requires a dialogical approach and mediation involving all related parties. Furthermore, revising the Joint Ministerial Regulation (PBM) on the establishment of places of worship is an urgent need to prevent discrimination and ensure the protection of human rights. This study also highlights the importance of active roles played by non-governmental organizations (NGOs) and the media in addressing issues of religious freedom. This research provides a significant contribution to understanding the dynamics of actors in religious conflicts and their implications for public policy in Indonesia. Abstrak Dinamika aktor dalam kebijakan penutupan rumah ibadah Gereja Kristen Indonesia (GKI) Yasmin di Kota Bogor pada periode 2006-2022. Fokus penelitian adalah untuk menganalisis peran aktor-aktor utama, faktor penyebab konflik, dan dampak kebijakan terhadap kebebasan beragama di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus melalui wawancara mendalam, observasi, dan analisis dokumen. Hasil penelitian menunjukkan bahwa konflik ini disebabkan oleh dugaan pelanggaran administratif dalam pengajuan Izin Mendirikan Bangunan (IMB), resistensi masyarakat terhadap keberadaan gereja, dan kebijakan pemerintah daerah yang kurang mendukung keberagaman. Faktor lain yang turut memengaruhi adalah kurangnya edukasi masyarakat tentang pentingnya toleransi beragama serta lemahnya komunikasi antara pemerintah, masyarakat, dan jemaat GKI Yasmin. Konflik ini mencerminkan ketegangan mayoritas-minoritas yang diperburuk oleh lemahnya regulasi terkait pendirian rumah ibadah. Keputusan Mahkamah Agung yang mendukung GKI Yasmin tidak dapat diimplementasikan karena tekanan sosial dan politik di tingkat lokal. Penyelesaian konflik berbasis hukum memerlukan pendekatan dialogis dan mediasi yang melibatkan seluruh pihak terkait. Selain itu, revisi Peraturan Bersama Menteri (PBM) tentang pendirian rumah ibadah menjadi kebutuhan mendesak untuk mencegah diskriminasi dan memastikan perlindungan hak asasi manusia. Penelitian ini juga menyoroti pentingnya peran aktif lembaga swadaya masyarakat (LSM) dan media dalam mengawal isu-isu kebebasan beragama. Studi ini memberikan kontribusi penting dalam memahami dinamika aktor dalam konflik keagamaan serta implikasinya terhadap kebijakan publik di Indonesia. Kata Kunci: Dinamika aktor; GKI Yasmin; Kebebasan beragama; Kebijakan publik; dan Konflik keagamaan.